Preclinical PK investigation of a novel IDO1/TDO dual inhibitor—SHR9146 in mouse plasma and tissues by LC-MS/MS - Xiao, Mei; Zhong, Kan; Guo, Li; Li, Wei; Wang, Xiaoli; Qiu, Zhenjun; Hang, Taijun (Frontiers in Oncology, 2023)
Purpose: The aim of the present study was to established a liquid chromatography tandem mass spectrometry (LC-MS/MS) method for the determination of SHR9146, a novel IDO1/TDO dual inhibitor, in mice plasma and tissues, and to apply it to investigate the pre-clinical plasma pharmacokinetics and tissues distribution of SHR9146 in mice. Methods: Samples were spiked with the deuterated SHR9146-d4 as internal standard and pretreated with protein-precipitation extraction by methanol. The chromatographic separation was performed on a Venusil ABS C18 column (150×4.6mm, 5μm) with isocratic elution by 10mM ammonium acetate buffer containing 0.1% formic acid solution and methanol as mobile phases. The MS detection was conducted in positive electrospray ionization with multiple reaction monitoring at m/z 444.1/229.4 for SHR9146 and m/z 448.4/229.2 for the internal standard. Results: The method showed good linearity in the calibration range from 0.05 to 50.0 g/ml. Precisions (intra- and inter-run) were in the range from 0.5% to 5.1% and accuracies (RE) were between -3.0% and 4.4% for all the concentration levels. SHR9146 was stable in all the tested bio-samples with recoveries >90%. Pharmacokinetic parameters were obtained using non-compartmental analysis. SHR9146 has a half-life of 0.713 h when IV-injected, with CL 12mL/min/kg and Vd 0.666L/kg. After oral dosing from 20 to 80 mg/kg, Cmax (range from 8.751 to 12.893 μg/mL) and AUC0-t (range from 15.606 to 69.971 μg·h/mL) of SHR9146 showed dose proportionality. Other post oral pharmacokinetic parameters in plasma were as follows (n=6): Tmax 0.79 ± 0.36 h, t1/2 1.586 ± 0.853 h, CL 19.8 ± 0.9 mL/min/kg, Vd 3.427± 1.617 L/kg, and the absolute bioavailability of 54.2%  12.6% (range from 40.2% to 64.7%). Besides, SHR9146 was found to be absorbed rapidly and distributed widely and mainly in stomach, adrenal gland, liver and lung. Conclusions: The method was simple, sensitive, accurate and specific, and was successfully applied for pre-clinical pharmacokinetic and tissue distribution study of SHR9146 in mice. The results showed that SHR9146 had dose-independent kinetics in mice via oral administration and was absorbed rapidly and distributed widely. The study provides good basis for further drug development assessment.